Meaning in life and perceived quality of life in Switzerland: results of a representative survey in the German, French and Italian regions - Bernard, Mathieu (Health Qual Life Outcomes, 2015)
BACKGROUND: The concept of meaning in life (MIL) has become a central one in recent years, particularly in psycho-oncology and palliative care. The Schedule for Meaning in Life Evaluation (SMILE) has been developed to allow individuals to choose the life areas that they consider to be important for their own MIL. This approach relates to the “World Health Organisation” definition of quality of life (QOL) as an individual’s perception of his own position. The aims of this study were (i) to assess MIL in a representative sample of the Swiss population according to the three linguistic regions and (ii) to evaluate whether MIL constitutes a significant determinant of the perceived QOL. METHODS: A telephone survey of the Swiss population, performed by a professional survey company, was conducted between November and December 2013. The interview included the SMILE, perceived QOL (0–10) and health status (1–5), and various sociodemographic variables. In the SMILE, an index of weighting (IOW, 20–100), an index of satisfaction (IOS, 0–100), and a total SMILE index (IOWS, 0–100) are calculated from the areas mentioned by the participants as providing MIL. RESULTS: Among the 6671 telephonic contacts realized, 1015 (15 %) participants completed the survey: 405 French, 400 German and 210 Italian participants. “Family” (80.2 %), “occupation/work” (51 %), and “social relations” (43.3 %) were the most cited MIL-relevant categories. Italian participants listed “health” more frequently than German and French participants (50.4 % vs 31.5 % and 24.8 % respectively, χ(2) = 12.229, p = .002). Age, gender, education, employment, and marital status significantly influenced either the MIL scores or the MIL-relevant categories. Linear regression analyses indicate that 24.3 % of the QOL variance (p = .000) is explained by health status (B = .609, IC = .490-.728, p = .000), MIL (B = .034, IC = .028-.041, p = .000) and socioeconomic status (F = 11.01, p = .000). CONCLUSION: The major finding of our analysis highlights the positive and significant influence of MIL on the perceived QOL in a representative sample of a general, multilingual and multicultural population. This result indicates that the existential dimension is not only determinant for QOL in some critical life events, as shown e.g. in psycho-oncology and palliative care, but also in everyday life.